2011
DOI: 10.1016/j.marpolbul.2011.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated compounds in estuarine and coastal areas of north Bohai Sea, China

Abstract: a b s t r a c tPerfluorinated compounds (PFCs) in water, sediment, soil, and biota collected from estuarine and coastal areas of the north Bohai Sea, China, were determined by use of HPLC-MS/MS. Significant concentrations of PFCs were found in water (mean: 18.4 ng/l) and biologic samples (fish: 265 ng/g dw), while concentrations of PFCs in soils and sediments were less. The predominately detected compound was perfluorooctanesulfonate (PFOS), with a maximum concentration of 30.9 ng/l in water and 791 ng/g dw in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 56 publications
4
36
2
1
Order By: Relevance
“…Several studies have reported on the PFAS-derived pollutions, especially PFOA and PFOS, along the Chinese coastline (Cai et al, 2012b;So et al, 2004;Wang et al, 2011). The composition of ionic PFASs in surface water was significantly different geographically.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the PFAS-derived pollutions, especially PFOA and PFOS, along the Chinese coastline (Cai et al, 2012b;So et al, 2004;Wang et al, 2011). The composition of ionic PFASs in surface water was significantly different geographically.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorine chemical facilities along the Daling River are the major manufacture centers in North China. Previous studies in this area have reported the occurrence and wide distribution of PFASs in surface water, sediment, soil, and human serum (Bao et al 2011;Chen et al 2011;Wang et al 2011Wang et al , 2013. The transportation of PFASs in river system is considered as the main environmental transport way of PFASs.…”
Section: Introductionmentioning
confidence: 99%
“…The median modeled PFOS concentrations in fresh water, fresh water sediment and soil were 7.20 ng/L, 0.39 ng/g and 0.21 ng/g, respectively, in ES2 for the whole region, while the maximum concentrations were 47.10 ng/L, 4.98 ng/g and 2.49 ng/g. Measured concentrations of PFOS in samples from this region collected around 2010 were collated from literature sources (Bao et al, 2009;Li et al, 2011;Lu et al, 2012;Pan et al, 2011;Shi et al, 2012;Sun et al, 2011;Wang et al, 2011;Yang et al, 2011;Zhao et al, 2013). These data were compared with predicted concentrations in all emission scenarios as a preliminary model evaluation (Fig.…”
Section: Model Output and Validationmentioning
confidence: 99%
“…Much of the current research on PFOS risk analysis has focused on aquatic ecosystems, as they are the main receptor and transmission pathway for PFOS So et al, 2007;Steenland et al, 2009;Wang et al, 2012a;Wang et al, 2012b;Wang et al, 2011;Zhang et al, 2011;Zhang et al, 2012). In this study, the environmental risks of PFOS in this region were assessed by comparing the modeled concentrations with environmental quality criteria or standard values.…”
Section: Environmental Risksmentioning
confidence: 99%
See 1 more Smart Citation